Digitalisasi Manajemen Keuangan Melalui Aplikasi Buku Warung Untuk Meningkatkan Kemandirian Ekonomi Pesantren Jabal Rahmah, Kabupaten Solok - Sanda Patrisia Komalasari; Alfairah Azmi; Muhammad Iqbal Abdi Lubis; Rizka Hadelina; Ainul Mardiah; Rizki Dafa Naldi; Rafki Harzikra; Bunga Jacinda; Khalilul Rahman (BULETIN ILMIAH NAGARI MEMBANGUN, 2025)
This activity aims to strengthen this independence by integrating digital technology solutions into the school's financial management system. The method used was a participatory qualitative approach with four main stages: preparation, implementation, mentoring, and evaluation. This process involved the active participation of the school's administrators. The implemented solution focused on the use of the digital application "Buku Warung" to simplify transaction recording, stock management, and financial reporting. The results showed a significant impact. Before the intervention, 100% of the recording was done manually, incomplete, and prone to errors. After mentoring, the boarding school administrators' understanding of digital and financial literacy improved substantially. Adoption of the application reached 95%, effectively transforming the recording system into a digital and detailed one. The time efficiency of preparing financial reports such as profit and loss and cash flow increased by 75%, enabling administrators to make faster and more accurate business decisions. Despite obstacles such as limited internet access at the site and initial resistance to change, these obstacles were successfully overcome through ongoing education and practical mentoring. The conclusion of this activity was that the combination of technological solutions and practical mentoring proved effective in improving the economic management capacity of Islamic boarding schools. To ensure the program's sustainability, it is recommended that Islamic boarding schools integrate all their business units into a single, integrated system and expand collaboration with various parties for further support.